Website Content Marketing and Tourists’ Visiting Decisions: : Evidence from Bhakti Alam Pasuruan Agrotourism - Cahyani Dwi Novianti; Nuriah Yuliati; Mirza Andrian Syah (Amkop Management Accounting Review (AMAR), 2026)
The low number of tourist visits to Bhakti Alam Pasuruan Agrotourism was previously related to the suboptimal quality of the website in terms of content, information presentation, and ease of discovery, which could hinder tourists in obtaining information and making decisions. The website improvements made in March 2025 cannot yet guarantee the effectiveness of the content on tourist behavior, so this study aims to analyze the influence of website content marketing on tourists' decisions to visit Bhakti Alam Pasuruan Agrotourism. The research uses primary data through surveys and interviews with 100 tourists who have accessed the latest version of the bhaktialam.co.id website. Sampling was done using purposive sampling, while data analysis was done using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method to test the direct influence of content marketing variables on visiting decisions. The results of the study indicate that content marketing on the website has a positive and significant effect on tourists' decisions to visit. Agrotourism managers need to continue to improve the quality and consistency of content so that the website can function as an official source of information for potential tourists. content so that the website can function as an official source of information for potential tourists.